Musculoskeletal and Visceral Quality of Broilers with Different Body Patterns - J Leite dos Santos; L Amoroso; FC Silverio; AV Costa; MC Silva; SMB Artoni; GC Costa; MS Rubio (Brazilian Journal of Poultry Science)
ABSTRACT The growth pattern of broilers can be influenced by diets, environment, stress, health and management. Considering the relevance of the body structure of broilers for slaughterhouse condemnations, the aim of this study was to analyze the body composition, bone mineral density (BMD), and musculoskeletal and visceral morphology of broilers with different body attributes from commercial slaughterhouses. Forty-eight plucked broilers from two different strains were distributed into three groups: standard, uneven, and cachectic. The broilers were evaluated for lean mass, body fat, BMD, and bone mineral content (BMC), and subject to macroscopic, musculoskeletal and visceral analyses. It was found that BMD was lower in the uneven and cachectic groups compared to the standard (p≤0.05), and cachectic broilers had a lower BMC compared to the other groups. The body weight of broilers in the standard group was greater compared to the other groups, while the relative weight of the proventriculus, gizzard, liver, duodenum, jejunum, cardiovascular structures, and kidney was greater among the cachectic in comparison to the others. The uneven group presented intermediate mean values for several densitometric and morphological parameters, as well as no statistical difference (p≥0.05) to the standard group in the weight of the proventriculus, spleen and kidneys, the weight and the length of duodenum, the length and diameter of the gastrocnemius, and the diameter of the sartorius muscle. It is possible to conclude that uneven broilers have similar characteristics to the standard group, demonstrating that they could be used as feedstock for processed products, reducing economic losses at the slaughterhouse.